Resonance raman and FTIR studies of carbon monoxide-bound cytochrome aa3-600 oxidase of bacillus subtilis - Vamvouka, Magdalini; Varotsis, Constantinos (My University, 1998)
Resonance Raman and FTIR spectra are reported for the fully reduced carbon monoxy derivative of the quinol aa3-600 oxidase from Bacillus subtilis. The resonance Raman spectra display two isotope-dependent vibrational modes at 520 and 575 cm-1. The FTIR spectrum displays a single vibrational mode at 1963 cm-1. We assign the band at 520 cm-1 to the Fe-CO stretching mode, the band at 575 cm-1 to the Fe-C-O bending mode, and the band at 1963 cm-1 to the C-O stretching mode. The frequencies of these modes are similar to those that have been reported for the CO-bound mammalian cytochrome c oxidase. Despite the fact that two different heme-protein conformations that affect the iron-his bond strength are present in the ferrous ligand-free form of aa3-600, the CO-bound adduct has a single conformation in which the His-Fe-CO CUB moiety has the same structure as the α form found in the mammalian cytochrome c oxidase. The present and previous data on the vibrational frequencies of ferrous ligand-free and ferrous CO-bound forms of terminal oxidases show that an inverse linear relationship exists between the frequencies of the Fe-his and Fe-CO stretching modes. We suggest that the frequencies of both the Fe-CO and C-O modes found in heme-CUB oxidases are affected by the proximal His376, which is H-bonded to the peptide carbonyl of Gly351, and by distal effects on the heme a3-bound CO exerted by CuB
Keywords: Fourier transform infrared spectroscopy; Carbon; Cytochrome oxidase; Bacillus subtilis; Heme; Ligands; Chemistry